Exoskeleton kinematic design robustness: An assessment method to account for human variability. (4th November 2020) - Sposito, Matteo; Di Natali, Christian; Toxiri, Stefano; Caldwell, Darwin G.; De Momi, Elena; Ortiz, Jesús
Abstract: Exoskeletons are wearable devices intended to physically assist one or multiple human joints in executing certain activities. From a mechanical point of view, they are kinematic structures arranged in parallel to the biological joints. In order to allow the users to move while assisted, it is crucial to avoid mobility restrictions introduced by the exoskeleton's kinematics. Passive degrees of freedom and other self-alignment mechanisms are a common option to avoid any restrictions. However, the literature lacks a systematic method to account for large inter- and intra-subject variability in designing and assessing kinematic chains. To this end, we introduce a model-based method to assess the kinematics of exoskeletons by representing restrictions in mobility as disturbances and undesired forces at the anchor points. The method makes use of robotic kinematic tools and generates useful insights to support the design process. Though an application on a back-support exoskeleton designed for lifting tasks is illustrated, the method can describe any type of rigid exoskeleton. A qualitative pilot trial is conducted to assess the kinematic model that proved to predict kinematic configurations associated to rising undesired forces recorded at the anchor points, that give rise to mobility restrictions and discomfort on the users.